ICT enhanced learning for older adults: Influencing factors on satisfaction and the role of learning motivation - Lipphardt, Anne-Marie; Held, Paul; Leen-Thomele, Eline; Hain, Lukas (Gerontechnology, 2018)
PURPOSE. Since Lifelong Learning has become a guiding principle of educational policy in many countries across the globe, several concepts in the field of educational gerontology were developed and implemented. In this context, also learning opportunities through ICT were tested and studies have proven a high suitability of e-learning for older people and their potentials for digital inclusion (1, 2, 3). Yet, little research has been done about the influence of learning motivation, personality traits and demographical aspects on e-learning success. METHOD. This paper discusses the results of the implementation and evaluation of four e-learning programs on ICT, culture, mentoring and well-being for older adults with 128 people (94 females, 34 males; mean age 67,12 years, SD 10,485) from five European countries. As part of the evaluation, satisfaction with course preparation and support, information on learning motivation, and aspects of e-learning as method were queried and analyzed with focus on differences with regards to gender, age, nationality, educational level, experience with ICT, life satisfaction, and health status. Learning motivation was further divided into motives of belonging, personal growth, instrumentality, and competition (4). RESULTS AND DISCUSSION. Findings show that older adults across all distinguishing criteria cope very well with diverse aspects of e-learning and highly benefit from the given advantages. No significant differences were found when comparing the subgroups. These results confirm study findings done at national level on suitability of e-learning (5). Differences could be found in learning motivation with regards to age, nationality, health status, gender. Younger participants take part more often for motives of competition, instrumentality and social belonging and older participants for motives of personal growth. Cross-country comparisons show significant differences with regards to diverse aspects in learning motivation. While personal growth was most important for German and Spanish participants, for participants from Finland motives of competition meant the most. As regards gender, men were more likely to take part for reasons of social belonging and instrumentality than women. Overall, results trigger considerations to develop e-learning programs adaptable to certain sub-groups (e.g. country-specific elements). <
Keywords: ICT; educational gerontology; e-learning: learning motivation